Role of the range of the dipole function in the classical dynamics of molecular dissociation - De Lima, Emanuel F. [UNESP]; Ramos, Tárcius N. [UNESP]; De Carvalho, R. Egydio [UNESP] (American Physical Society (APS), 2013)
The dissociation dynamics of heteronuclear diatomic molecules induced by infrared laser pulses is investigated within the framework of the classical driven Morse oscillator. The interaction between the molecule and the laser field described in the dipole formulation is given by the product of a time-dependent external field with a position-dependent permanent dipole function. The effects of changing the spatial range of the dipole function in the classical dissociation dynamics of large ensembles of trajectories are studied. Numerical calculations have been performed for distinct amplitudes and carrier frequencies of the external pulses and also for ensembles with different initial energies. It is found that there exist a set of values of the dipole range for which the dissociation probability can be completely suppressed. The dependence of the dissociation on the dipole range is explained through the examination of the Fourier series coefficients of the dipole function in the angle variable of the free system. In particular, the suppression of dissociation corresponds to dipole ranges for which the Fourier coefficients associated with nonlinear resonances are null and the chaotic region in the phase space is reduced to thin layers. In this context, it is shown that the suppression of dissociation of heteronuclear molecules for certain frequencies of the external field is a consequence of the finite range of the corresponding permanent dipole. © 2013 American Physical Society.
Keywords: Angle variables; Carrier frequency; Chaotic regions; Classical dynamics; Dissociation dynamics; Dissociation probability; External fields; Fourier coefficients; Heteronuclear diatomic molecule; Heteronuclear molecules; Initial energy; Laser fields; Molecular dissociation; Morse oscillator; Nonlinear resonance; Numerical calculation; Permanent dipoles; Phase spaces; Thin layers; Time-dependent; Dynamics; Fourier analysis; Molecules; Phase space methods; Dissociation